IMPROVEMENT OF PRODUCT POLICY AT THE ENTERPRISE IN THE CONDITIONS OF INNOVATIVE ECONOMY - Shakarov Allayor Baratovich; Egamkulov Davlatbek Bahodir o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the improvement of product policy at an enterprise in the context of an innovative economy. The importance of effective product policy for successful competition in the market is considered, as well as the adaptation of product policy strategies to the changing requirements and opportunities provided by innovation. The main aspects of the development and implementation of product policy in the conditions of an innovative economy are analyzed, including the choice of assortment, pricing, promotion and distribution of products.